2014
DOI: 10.1007/s10899-014-9447-4
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Gambling Among Emerging Adult Males in French-Speaking Switzerland

Abstract: The aims were twofold: to examine the gambling habits of emerging adult males in the French-speaking regions of Switzerland and to what extent these habits predict problem gambling within this population. We also evaluated problem gambling rates and provided data concerning variables such as gambling location, level of information about problem gambling and awareness of treatment centers. 606 Swiss male conscripts, aged 18-22 years, completed a self-report questionnaire. This was administered during their army… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
2
10
2
1
Order By: Relevance
“…Results showed that about 55% of the sample reported gambling in the previous twelve months. This prevalence is similar to the rates observed by Tomei et al (2014) in 18-22 year-old French-speaking men (56.1%) and by Inglin and Gmel (2011) in the French-speaking adult population (56.8%), suggesting that gambling is a popular activity in Switzerland. Moreover, although low, the prevalence of DSM-5 gambling disorder observed in the present study (1.0 of the total sample, 1.7% of gamblers) is slightly higher than the rates of pathological gambling (1.4% of gamblers) observed by Tomei et al (2014) in a comparable sample of Swiss French-speaking young men, and is about twice the prevalence of pathological gambling (0.5%) reported by Bondolfi et al (2008) in the Swiss adult population.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Results showed that about 55% of the sample reported gambling in the previous twelve months. This prevalence is similar to the rates observed by Tomei et al (2014) in 18-22 year-old French-speaking men (56.1%) and by Inglin and Gmel (2011) in the French-speaking adult population (56.8%), suggesting that gambling is a popular activity in Switzerland. Moreover, although low, the prevalence of DSM-5 gambling disorder observed in the present study (1.0 of the total sample, 1.7% of gamblers) is slightly higher than the rates of pathological gambling (1.4% of gamblers) observed by Tomei et al (2014) in a comparable sample of Swiss French-speaking young men, and is about twice the prevalence of pathological gambling (0.5%) reported by Bondolfi et al (2008) in the Swiss adult population.…”
Section: Discussionsupporting
confidence: 82%
“…In European countries, twelve-month prevalence rates of pathological gambling ranged from 0.15% to 0.60% in the adult population (Sassen et al 2011), including 0.50% in Switzerland (Bondolfi et al 2008) and prevalence rates of problem 4 gambling ranged from 0.25% to 1.40% (Sassen et al 2011), including 0.80% in Switzerland (Bondolfi et al 2008). Thus, gambling constitutes an important public health problem, particularly in emerging adults and males -a population in which excessive gambling is overrepresented (Tomei et al 2014;Tozzi et al 2013;Luder et al 2010; see Williams et al 2012, for review).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study [18] conducted in the French part of Switzerland on a sample of conscripts (aged 18-24 years), the prevalence rate of problem gambling was 1.4% according to the Problem Gambling Severity Index [24]. In another study conducted in the French part of Switzerland, prevalence of at-risk gambling was 5.5% in a sample of adolescents aged 14-17 years, based on the SOGS [19].…”
Section: Problematic Gamblingmentioning
confidence: 95%
“…According to the Swiss Health Census [16], the life-time and past-year prevalence of gambling among the Swiss adult population in 2012 [17] was 73.6 and 46.6%, respectively. In a study conducted in male conscripts (military service is mandatory in Switzerland) aged 18-22 years [18], 79% of the respondents were lifetime gamblers and 56% were past-year gamblers. The reported prevalence of gambling among 14-17-year-olds was 37.48% [19].…”
Section: Gambling Prevalencementioning
confidence: 99%
See 1 more Smart Citation